Fundamentals of astrophysics astrophysical methods - Ferrari, Attilio 1941- (UNITEXT for physics, 2024)
This book illustrates how the study of astrophysics requires training in several fields of physics, mathematics and technology. Based on the author’s extensive teaching experience, it focuses on the basic observational data and theoretical methods used to build models for stars, galaxies and large-scale structures in the universe. Part I deals discusses gravitational theories, including basic general relativity and gravitational waves. In turn, Part II illustrates the radiation and plasma processes that are fundamental to interpreting the observed data and to modeling cosmic objects. Part III addresses the observational techniques needed in astrophysics, and the analysis of astrophysical parameters derived from photometry and spectroscopy. The book also includes an introduction outlining the historical development of the study of the universe, and a concluding chapter summarizing the physical properties of cosmic objects.